Auditing Peta Medan Kuman dan Antibiogram sebagai Educated-guess Penanganan Penyakit Infeksi - Hendro Wahjono; Tri Nur Kristina (MEDIA MEDIKA INDONESIANA, 2008)
ABSTRACTBacterial mapping and antibiogran as an educated quess in the management of infectious diseasesBackground: Facing infectious disease problems, rational diagnosis is needed using a foundation of theoretical and concept of clinical microbiology. Surveillance of bacterial mapping and susceptibility of antibiotics should be done routinely and reported as educated-guess.Methods: This was a descriptive study using secondary data from medical record of blood culture and sensitivity test from intensive care units Dr. Kariadi hospital, Semarang in 2005 and 2006.Results: There were several chages in bacterial mapping of blood culture from year 2005 and 2006. Bacterial mapping in ICU and PICU, which in 2005 was dominated by Gram (-) rods changed to Gram (+) cocci in 2006. This study also showed the decreasing effectivity of third and fourth generation of ceholosporin, and carbapenem that offenly used in intensive care units.Conclusion: Changes of bacterial mapping and antibiotic resistance can be caused by overuse and/or misuse of antibiotics therapy or prophylaxis. There should be a better coordination among members of the infectious desease control.Key Words: Bacterial mapping, sensitivity, antibiotics.ABSTRAKLatar belakang: Diagnosis rasional dengan menggunakan landasan teori dan konsep mikrobiologi klinik sangat diperlukan dalam menghadapi masalah medis yang berhubungan dengan infeksi. Survei peta medan kuman dan kepekaan antibiotik yang sering digunakan di RS perlu dilaksanakan secara rutin agar klinisi mempunyai pedoman dalam merancang alternatif tindakan dan terapi antibiotik pilihan.Metode: Penelitian ini merupakan studi deskriptif dengan data skunder dari catatan medik pemeriksaan kultur darah dan tes sensitiviti dari pasien rawat inap di unit perawatan intensif RS Dr Kariadi Semarang pada tahun 2005 dan 2006.Hasil: Gambaran peta medan kuman dari material klinik darah menunjukkan perubahan rangking populasi kuman dari tahun 2005 dan 2006. Peta medan kuman di ICU dan PICU yang pada tahun 2005 didominasi oleh kuman batang Gram (-), pada tahun 2006 berubah menjadi kuman coccus Gram (+). Hasil antibiogram tahun 2006 dari ICU menunjukkan terjadinya penurunan efektifitas antibiotika cephalosporin generasi III, IV, dan carbapenem yang lazim digunakan di unit-unit perawatan intensif.Simpulan dan Saran: Perubahan peta medan kuman dan turunnya efektifitas berbagai antibiotik kemungkinan diakibatkan oleh pemberian terapi atau profilaksis antibiotik yang kurang tepat atau bahkan berlebihan dalam penggunaannya. Perlu peningkatan kerjasama dari tim penanganan penyakit infeksi untuk mengatasi masalah tersebut.